IMPLEMENTASI PENGUATAN PENDIDIKAN KARAKTER DI MASA PEMBELAJARAN JARAK JAUH (PJJ) PADA JENJANG SD/MI - Nurul Aini; Machfudzil Asror (Universitas Negeri Surabaya, 2022)
The purpose of the survey research on the implementation of strengthening character education (PPK) during Distance Learning (PJJ) is to describe the implementation of PPK during PJJ at the SD/MI level throughout Sidoarjo Regency by conducting surveys to teachers, classroom teachers and principals of SD/MI in 18 sub-districts. in Sidoarjo district, by using a questionnaire in the form of a google form. The data obtained from 192 teachers, classroom teachers and principals of SD/M were analyzed descriptively. The results obtained are the implementation of the 5 values of PPK as stated in Permendikbud No. 20 of 2018 was carried out even though it was in PJJ conditions by making efforts that were adapted to online and offline learning